Increasing the prosthodontic awareness of an aging Indian rural population - Swapnil Parlani; Arvind Tripathi; Saumyendra Vikram Singh (Wolters Kluwer Medknow Publications, 2011)
Objective: The aged are prone to biological, social, and psychological problems, especially those residing in the rural areas. The rural aging population in contrast to their urban counterparts is illiterate, poor, and ignorant; cumulative is the fact that the youth are leaving rural areas for money and better opportunity to urban areas. An educational and motivational program to increase prosthodontic awareness was therefore undertaken and it was studied whether this translated into an increased demand for prosthodontic services. Materials and Methods: The study area consisted of a group of six villages collectively known as "Sarora" situated in Lucknow, Uttar Pradesh, India. The study population was divided on the basis of age, sex, education, and economic status and comparisons were made in between these groups. Interview and clinical examination were the tools of the study. Data were collected before and after the educational program and was subjected to statistical analysis. Results: The educational program led to more subjects adopting tooth brushing and neem twig chewing as a method of oral hygiene maintenance. The prosthodontic need fulfillment increased from 3.5% before the program to 13.6% after education and motivation. Conclusion: It was concluded that mobile dental clinics, dental camps, and prosthodontic outreach programs could be solutions to spread awareness and disseminate treatment.